Peran Dinas Sosial dalam Mendampingi Anak Yang Berkonflik Dengan Hukum di Kota Palangka Raya - Salsabila; Syarifudin; Angelia, Novita Mayasari (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2025)
The assistance of children in conflict with the law by the PalangkaRaya City Social Service is the implementation of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA Law), which prioritizes a restorative justice approach. This program aims to ensure the protection of children's rights, including the right to identity, rehabilitation, and social reintegration. Although there has been coordination between agencies, challenges such as limited facilities and human resources still hinder the effectiveness of mentoring. This study uses a qualitative approach with a focus on the role of the Social Service in assisting children involved in criminal acts. The findings show that mentoring is carried out through various mechanisms such as social advocacy, counseling, mediation, and social rehabilitation. However, the main obstacle in the implementation of this program is the lack of facilities of the Social Welfare Organizing Institution (LPKS) and the limitation of professionals, such as child psychologists. In addition, the lack of support from the family is also an obstacle in the rehabilitation of children. Collaboration between the Social Service, law enforcement officials, and educational institutions is needed to create more comprehensive assistance. This study suggests that facilities and human resources should be improved, as well as strengthen the role of families in the child rehabilitation process. With this approach, it is hoped that children who are in conflict with the law can have the opportunity for better recovery, without neglecting the rights of the victim. Keywords: Child Assistance, Juvenile Criminal Justice System, Social Services